Submetering as an instrument of water demand management in building systems: a case study at the University of São Paulo - Tamaki, Humberto Oyamada (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This research work discusses the use of submetering as an instrument for water demand management in building systems. The characterization of meters and the study of the interactions of its elements with plumbing systems have been carried out, based on both systems and the building performance approaches. Considering the need for improving both qualitative and quantitative data collection on water consumption, which is essential for demand management, especially in a context of rational water usage, different systems and technologies for remote reading have been investigated. A proposal for planning the submetering implementation is described, indicating the elements that shall be considered for demand management. A case study on the submetering program at the University of São Paulo was undertaken, in which it was possible to confirm its importance and to observe the extremely positive results that had justified its implementation.